Pemanfaatan Alat Tekan Penetrasi Modifikasi Paving Block Untuk Melihat Nilai Kuat Tekan Yang Dipengaruhi Oleh Waktu Perendaman Menggunakan Tanah, Semen, Dan Kapur - Aldani, Muhammad; Iswan, Iswan; Setyanto, Setyanto (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2017)
Soil sample that used as base material in this study was taken from Belimbing Sari Village area, Sub Jabung, East Lampung. Based on the testing of soil physical's characteristics, USCS classified soil samples as organic soil with medium to high plasticity and belongs to the OH group. The mixed content which used in this study was 85% soil, 10% lime, and 5% cement with curing time for 14 days, then it was divided with combustion and without combustion treatment on the paving block sample and soaked for 4, 8, 12, and 16 days. The result of this study was to obtain the average value of pressed-value on a mixture of 85% soil + 10% lime + 5% cement after the largest burning treatment and soaked for 4 days at 11.7 MPa. Thus, in addition to the combustion, the duration of immersion also affects its pressed-value. The longer it had soaked, the smaller its pressed-value would be. Therefore, this pressed-value met the requirement of the paving blocks' SNI-03-0691-1996 that was qualified on the classification of quality D which had the average pressed-value of at least 10 MPa. In addition to the pressed-value, the water absorption rate which was 15.5% -20.32% did not meet the paving blocks' requirement of SNI-03-0691-1996.Key words : Paving block, organic clay soil, compressive strength, water absorption, immersion.